2020
DOI: 10.1002/adma.202000036
|View full text |Cite
|
Sign up to set email alerts
|

Silicon‐Nanotube‐Mediated Intracellular Delivery Enables Ex Vivo Gene Editing

Abstract: Engineered nano–bio cellular interfaces driven by vertical nanostructured materials are set to spur transformative progress in modulating cellular processes and interrogations. In particular, the intracellular delivery—a core concept in fundamental and translational biomedical research—holds great promise for developing novel cell therapies based on gene modification. This study demonstrates the development of a mechanotransfection platform comprising vertically aligned silicon nanotube (VA‐SiNT) arrays for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 50 publications
(72 reference statements)
2
87
0
Order By: Relevance
“…[ 36,116,163 ] Using fluorescence staining and confocal imaging, components of multiple endocytic pathways such as clathrin light chain, caveolin‐1, DNM2, and CLTA have also been observed to coassemble at highly curved cell membranes along VNS (Figure 9e). [ 12,36,116,167 ] An inhibition study treated GPE86 cells with nystatin and chloropromazine, finding that nystatin (which suppresses formation of lipid rafts, cholesterol‐enriched domains, and caveolae) caused greater impairment of Si nanotube‐mediated mRNA delivery than chloropromazine (which inhibits clathrin‐mediated endocytosis and interferes with fast endophilin‐mediated endocytosis). [ 12 ] But for primary immune cells, especially for lymphocytes, endocytic pathways are often carefully gated via foreign element detectors such as TLR.…”
Section: Vns‐mediated Intracellular Delivery Into Immune Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 36,116,163 ] Using fluorescence staining and confocal imaging, components of multiple endocytic pathways such as clathrin light chain, caveolin‐1, DNM2, and CLTA have also been observed to coassemble at highly curved cell membranes along VNS (Figure 9e). [ 12,36,116,167 ] An inhibition study treated GPE86 cells with nystatin and chloropromazine, finding that nystatin (which suppresses formation of lipid rafts, cholesterol‐enriched domains, and caveolae) caused greater impairment of Si nanotube‐mediated mRNA delivery than chloropromazine (which inhibits clathrin‐mediated endocytosis and interferes with fast endophilin‐mediated endocytosis). [ 12 ] But for primary immune cells, especially for lymphocytes, endocytic pathways are often carefully gated via foreign element detectors such as TLR.…”
Section: Vns‐mediated Intracellular Delivery Into Immune Cellsmentioning
confidence: 99%
“…[ 12,36,116,167 ] An inhibition study treated GPE86 cells with nystatin and chloropromazine, finding that nystatin (which suppresses formation of lipid rafts, cholesterol‐enriched domains, and caveolae) caused greater impairment of Si nanotube‐mediated mRNA delivery than chloropromazine (which inhibits clathrin‐mediated endocytosis and interferes with fast endophilin‐mediated endocytosis). [ 12 ] But for primary immune cells, especially for lymphocytes, endocytic pathways are often carefully gated via foreign element detectors such as TLR. [ 168 ] It was reported that delivery of genetic agents using SiNWs did not activate endocytic or inflammatory pathways.…”
Section: Vns‐mediated Intracellular Delivery Into Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanostructure substrates ( Figure 2E) are a group of methods utilizing 1D structures such as nanoneedles, [107,110] nanowires, [111][112][113][114][115][116][117] nanotubes, [118,119] and nanostraws [120][121][122][123] with diameters small enough that when cells are adhered to them they either induce spontaneous penetration, alter membrane permeabilization, or elicit endocytosis for molecular delivery. There is an ongoing debate as to which of these mechanisms or combination of mechanisms is primarily responsible for delivery using nanostructures.…”
Section: Engineered Substrate Methodsmentioning
confidence: 99%